Parental and Community Involvement in Children’s Transition from Pre- Primary School to Class One in Soy Division, Eldoret West District, Uasin Gishu County - Koskey , Selina J.; Kafu , Patrick; Syomwene , Anne (African Journal of Education,Science and Technology (AJEST), 2013)
Although the Ministry of Education has worked in collaboration with various partners to ensure that all children get access to education in a child friendly environment, the enrolment rates in class 1 in primary schools has continued to show some disparities as compared to those of other lower primary school class levels in soy division. This paper is a report of a study that was carried out in 2012 in Soy Division of Eldoret West District in Uasin Gishu County to investigate the extent to which parental and community involvement influence children’s transition from pre-primary to class one in the division. The study was guided by Bronfenbrenner’s Ecological Systems theory and adopted a descriptive survey design. Stratified and simple random sampling techniques were used to select 14 private and 22 public schools. The respondents were head teachers, Parent Teacher Association chair-persons, class one and pre-primary school teachers from the sampled schools. Questionnaires and interview schedules were used in data collection. Obtained data was analysed using descriptive and inferential statistics. The study findings revealed that; the parents and the entire community of Soy Division never provided common roles in the two class levels under study. Majority of pre-primary parents escorted their children to school as compared to class one parents. Most parents in the pre-primary provided essentials for the school feeding programme unlike their counterparts in class one. The community never organized graduation ceremonies for those children moving to class one. The study therefore recommended that there was need for the parents’ mobilization so that they could get to understand children’s developmental needs and that the Ministry of Education should organize for more fund allocation to allow for community mobilization and training on the children’s transition.